The imperative for regenerative agriculture. (1st March 2017) - Rhodes, Christopher
A review is made of the current state of agriculture, emphasising issues of soil erosion and dependence on fossil fuels, in regard to achieving food security for a relentlessly enlarging global population. Soil has been described as "the fragile, living skin of the Earth", and yet both its aliveness and fragility have all too often been ignored in the expansion of agriculture across the face of the globe. Since it is a pivotal component in a global nexus of soil-water-air-energy, how we treat the soil can impact massively on climate change – with either beneficial or detrimental consequences, depending on whether the soil is preserved or degraded. Regenerative agriculture has at its core the intention to improve the health of soil or to restore highly degraded soil, which symbiotically enhances the quality of water, vegetation and land-productivity. By using methods of regenerative agriculture, it is possible not only to increase the amount of soil organic carbon (SOC) in existing soils, but to build new soil. This has the effect of drawing down carbon from the atmosphere, while simultaneously improving soil structure and soil health, soil fertility and crop yields, water retention and aquifer recharge – thus ameliorating both flooding and drought, and also the erosion of further soil, since runoff is reduced. Since food production on a more local scale is found to preserve the soil and its quality, urban food production should be seen as a significant potential contributor to regenerative agriculture in the future, so long as the methods employed are themselves 'regenerative'. If localisation is to become a dominant strategy for dealing with a vastly reduced use of fossil fuels, and preserving soil quality – with increased food production in towns and cities – it will be necessary to incorporate integrated ('systems') design approaches such as permaculture and the circular economy (which minimise and repurpose 'waste') within the existing urban infrastructure. In addition to growing food in urban space, such actions as draught-proofing and thermally insulating existing building stock, and living/ working on a more local scale, would serve well to cut our overall energy consumption. In order to curb our use of fossil fuels, methods for reducing overall energy use must be considered at least equally important to expanding low-carbon energy production. In synopsis, it is clear that only by moving from the current linear, 'take, make, dispose (waste-creation)' model for resource-consumption, to the systemic, circular alternative of 'reduce, reuse, recycle, regenerate', are we likely to meet demands for future generations.